2011
DOI: 10.1007/s10811-010-9632-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds in seaweed: functional food applications and legislation

Abstract: Seaweed is more than the wrap that keeps rice together in sushi. Seaweed biomass is already used for a wide range of other products in food, including stabilising agents. Biorefineries with seaweed as feedstock are attracting worldwide interest and include low-volume, high valueadded products and vice versa. Scientific research on bioactive compounds in seaweed usually takes place on just a few species and compounds. This paper reviews worldwide research on bioactive compounds, mainly of nine genera or species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
1,303
10
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,579 publications
(1,476 citation statements)
references
References 348 publications
43
1,303
10
12
Order By: Relevance
“…In addition, the market value for seaweed biomass as biofuel is low compared with other product types (Skjermo et al 2014). Seaweed biomass is a rich source of a wide range of bioactive products of potentially high market value (Holdt and Kraan 2011). Relevant applications include (i) human food, (ii) domestic animal and fish feed products, (iii) fertilizer, (iv) prebiotics, (v) cosmetics, (vi) bioactive peptides and (vii) pharmaceuticals and nutraceuticals, and these are predicted to play an important role in the emerging Norwegian bio-economy based on seaweed cultivation (Skjermo et al 2014).…”
Section: Product Applications-industrial Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the market value for seaweed biomass as biofuel is low compared with other product types (Skjermo et al 2014). Seaweed biomass is a rich source of a wide range of bioactive products of potentially high market value (Holdt and Kraan 2011). Relevant applications include (i) human food, (ii) domestic animal and fish feed products, (iii) fertilizer, (iv) prebiotics, (v) cosmetics, (vi) bioactive peptides and (vii) pharmaceuticals and nutraceuticals, and these are predicted to play an important role in the emerging Norwegian bio-economy based on seaweed cultivation (Skjermo et al 2014).…”
Section: Product Applications-industrial Perspectivesmentioning
confidence: 99%
“…Moreover, seaweeds contain a large variety of phytochemical constituents that can be used in the prevention and treatment of health diseases by various mechanisms (Holdt and Kraan 2011;Brown et al 2014). Bioactive compounds of interest include polysaccharides (e.g.…”
Section: Product Applications-industrial Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The richness of the algae in minerals, vitamins, bioactive substances, proteins, lipids and polyphenols with antibacterial, antiviral and antifungal properties points to the potential as a supplement in functional foods or as a raw material for the extraction of bioactive compounds (Holdt & Kraan, 2011). Fayaz et al (2005) analyzed K. alvarezii for its chemical composition and found that this species is rich in protein (16.2% w/w), fiber (29.4% w/w) and carbohydrates (27.4% w/w), with a high proportion of unsaturated fatty acids (44.5% of the total; 11.0% oleic acid, 13.5% cisheptadecenoic acid, 2.3% linoleic acid) and saturated fatty acids (37.0%, composed mainly of heptadecanoic acid).…”
Section: Carrageenan As a Dietary Fiber And Its Antiviral And Anti-camentioning
confidence: 99%
“…exhibited reducing power and hydroxyl radical scavenging activity higher than that of standard antioxidants. This antioxidant activity is of particular interest for cosmetic and pharmacological applications (Holdt & Kraan, 2011). Fayaz et al (2005) analyzed the antioxidant activity of extracts of K. alvarezii and observed that the chloroform:methanol (2:1) extract had 82.5% hydroxyl radical scavenging activity, while the acetone extract had 46.04% scavenging activity, both at a concentration of 1000 ppm.…”
Section: Kappaphycus Alvarezii Potential As a Cholesterol Reducer Andmentioning
confidence: 99%